Menekan Pengeluaran Belanja Harian Sayur Rumah Tangga: Sebuah Pelatihan Pembuatan Media Tanam Sayuran untuk Budidaya Polybag - Avisema Sigit Saputro; Efi Nikmatu Solihah (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2023)
Training on making planting media for polybags was held in Sanggrahan, Wonorejo, Gondangrejo, Karanyanyar, and Central Java. The activity was held on June 3, 2023, and was attended by women from PKK RT 05 RW 18. The characteristic of Sanggrahan is almost the same as that of other urban areas, namely the lack of land for cultivating plants. The aim of this activity is to provide insight to PKK women about urban agriculture so that the remaining land in urban areas can still be cultivated using a polybag system. Residents can manage small areas of land to grow vegetable crops so that they can reduce their daily household expenditure on vegetables. To produce optimal plant growth, cultivation in polybags requires appropriate planting media that are easy for residents to make. The method of service activities involves providing material counseling and practical training on making planting media for polybags. We train participants on using easily available materials to create planting media. The materials used to make planting media are humus soil, compost, and husk charcoal in a ratio of 1:1:1. All ingredients are mixed evenly, then put into a polybag. Vegetable seeds that are ready to plant are put into polybags, and then regular maintenance is carried out so that they grow optimally. The size of the polybag varies depending on the type of plant being planted. To support the success and sustainability of this activity, regular evaluation and monitoring are carried out. The aim of this community service is that residents can meet their household vegetable needs by making planting media that is easy to obtain in polybags.